2018
DOI: 10.3390/cells7110196
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulation of the Immune System in HIV/HCV-Coinfected Patients According to Liver Stiffness Status

Abstract: Background: Advanced cirrhosis is related to alterations in immunity. We aimed to evaluate the levels of peripheral CD4+ T cells (Tregs) and plasma cytokine in patients coinfected with human immunodeficiency virus and hepatitis C virus (HIV/HCV) according to liver fibrosis stages [evaluated as liver stiffness measure (LSM)] and their linear relationship. Methods: We performed a cross-sectional study on 238 HIV/HCV-coinfected patients (119 had <12.5 kPa, 73 had 12.5–25 kPa, and 46 had >25 kPa). Peripheral T-cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 66 publications
3
8
0
Order By: Relevance
“…Although cART might help reduce the plasma inflammatory marker levels in HIV–HCV-coinfected patients, the markers may still remain much higher than healthy controls [ 23 ]. In line with our findings, elevated liver fibrosis was previously linked to increased biomarkers of inflammation in HIV–HCV-coinfected patients [ 24 , 25 ]. In the present study, we identified a mixed profile of elevated circulating inflammatory cytokines, chemokines, and growth factors, including IL-6, IL-10, IFN-γ, GM-CSF, and FGF-basic, among HIV–HCV-coinfected patients with advanced liver fibrosis.…”
Section: Discussionsupporting
confidence: 92%
“…Although cART might help reduce the plasma inflammatory marker levels in HIV–HCV-coinfected patients, the markers may still remain much higher than healthy controls [ 23 ]. In line with our findings, elevated liver fibrosis was previously linked to increased biomarkers of inflammation in HIV–HCV-coinfected patients [ 24 , 25 ]. In the present study, we identified a mixed profile of elevated circulating inflammatory cytokines, chemokines, and growth factors, including IL-6, IL-10, IFN-γ, GM-CSF, and FGF-basic, among HIV–HCV-coinfected patients with advanced liver fibrosis.…”
Section: Discussionsupporting
confidence: 92%
“…The search for non-invasive parameters to predict the fibrosis progression becomes an important goal for monitoring HIV/HCV co-infected patients. As indicated, co-infection with HIV and HCV demonstrated an immunosuppressive profile compared to HIV-mono-infection, and in advanced cirrhosis patients, (stiffness > 25 kPa), was associated with the lowest plasma values of T-helper 1 and T-helper 17 response[27]. Furthermore, transient elastography evaluated in a prospective study on a cohort of 154 HCV/HIV co-infected patients identified that elevated alanine amino aspartate (AST) level and liver stiffness at the baseline were increased in individuals under the risk of fibrosis progression[28].…”
Section: Hiv/hcv Co-infection Induced Liver Injurymentioning
confidence: 99%
“…Sixteen studies have evaluated the effect of both HIV mono‐infection and HIV/HCV co‐infection on inflammatory biomarkers. (Table and Table S4) The majority of studies have found that HCV co‐infection further increases the serum levels of IL‐6, IL‐10, and sTNFRI but decreases levels of CRP or hsCRP irrespective of liver function . Shah et al found that CRP levels fell with increasing IL‐6 levels suggesting attenuation of the CRP‐related IL‐6 response .…”
Section: Special Populationsmentioning
confidence: 99%
“…(Table 3 and Table S3) Among CHC patients, elevated levels of BNP, NT-proBNP, 50,51,67,99,[125][126][127][128][129] TnT, and TnI 103,128 have been observed compared to healthy controls. ( Table 4 and Table S4) The majority of studies have found that HCV co-infection further increases the serum levels of IL-6, 133-138 IL-10, 139 and sTNFRI 138 but decreases levels of CRP or hsCRP 133,134,136,[140][141][142] irrespective of liver function. 133 Shah et al found that CRP levels fell with increasing IL-6 levels suggesting attenuation of the CRP-related IL-6 response.…”
Section: Biomarkers Of Cardiac Dysfunctionmentioning
confidence: 99%